P-Benzoquinone-induced aggregation and perturbation of structure and chaperone function of α-crystallin is a causative factor of cigarette smoke-related cataractogenesis. (1st February 2018) - Chowdhury, Aritra; Choudhury, Aparajita; Chakraborty, Shruti; Ghosh, Arunava; Banerjee, Victor; Ganguly, Shinjini; Bhaduri, Gautam; Banerjee, Rajat; Das, Kalipada; Chatterjee, Indu B.
Graphical abstract: Highlights: Accumulation of p-benzoquinone is observed in smokers' lens protein with cataract. p-benzoquinone causes modification of chaperon function of αA-crystallin. p-benzoquinone is a causative factor for cigarette smoke-induced cataractogenesis Abstract: Cigarette smoking is a significant risk factor for cataract. However, the mechanism by which cigarette smoke (CS) causes cataract remains poorly understood. We had earlier shown that in CS-exposed guinea pig, p-benzoquinone (p-BQ) derived from CS in the lungs is carried by the circulatory system to distant organs and induces various smoke-related pathogeneses. Here, we observed that CS exposure caused accumulation of the p-BQ-protein adduct in the eye lens of guinea pigs. We also observed accumulation of the p-BQ-protein adduct in resected lens from human smokers with cataract. No such accumulation was observed in the lens of never smokers. p-BQ is a strong arylating agent that forms Michael adducts with serum albumin and haemoglobin resulting in alterations of structure and function. A major protein in the mammalian eye lens is αA-crystallin, which is a potent molecular chaperone. αA-crystallin plays a key role in maintaining the integrity and transparency of the lens. SDS-PAGE indicated that p-BQ induced aggregation of αA-crystallin. Various biophysical techniques including UV–vis spectroscopy, fluorescence spectroscopy, FT-IR, bis-ANS titration suggested a perturbation of structure and chaperone function of αA-crystallin upon p-BQ modification. Our results indicate that p-BQ is a causative agent involved in the modification of αA-crystallin and pathogenesis of CS-induced cataract. Our findings would educate public about the impacts of smoking on eye health and help to discourage them from smoking. The study might also help scientists to develop new drugs for the intervention of CS-induced cataract at an early stage.